Determining and modelling a complete time-temperature-transformation diagram for a Pt-based metallic glass former through combination of conventional and fast scanning calorimetry. (1st July 2022) - Frey, M.; Neuber, N.; Müller, M.; Gross, O.; Riegler, S.S.; Gallino, I.; Busch, R.
Graphical abstract: Image, graphical abstract Abstract: State of the art fast differential scanning calorimetry (FDSC) is used to complement conventional differential scanning calorimetry (DSC) studies about the isothermal time-temperature-transformation (TTT) diagram of the bulk metallic glass forming liquid Pt42.5 Cu27 Ni9.5 P21 to allow a comprehensive study of the crystallization kinetics of this system over a broad temperature range. FDSC and DSC data align well in the low-temperature region of the crystallization nose but show distinct discrepancies in the high-temperature region as the FDSC studies reveal faster crystallization times. The results are mathematically described and discussed based on the Johnson-Mehl-Avrami-Kolmogorov (JMAK) equation. Thereby, either homogeneous or heterogeneous nucleation is assumed, depending on the respective experimental conditions in FDSC and DSC studies. With this approach, the complete TTT diagram can be modelled as superposition of two sequential JMAK fits.